ACCESSIBILITY RIGHTS TO PUBLIC FACILITIES FOR DISABILITIES IN INDONESIA - Nurvianti, Dewi (Tadulako University, 2017)
The disabilities people in Indonesia, interacting with their environment experienced many obstacles, especially in accessing public facilities. To eliminate all these obstacles, the Government of Indonesia pursues one way of doing so by fulfilling the right to accessibility to public facilities for PwDs. Such fulfillment efforts begin by ratifying the International Convention on Persons with Disabilities that govern the fulfillment of those rights. In addition, the effort taken also to give birth to the national legislation about persons with disabilities namely Law No. 8 of 2016. In the Act is regulated one of several rights, namely the right to accessibility. In this article we will describe the right accesibiltas which is part of human rights and the availability of legal guarantees in Indonesia on the right to accessibility for persons with disabilities in some legislation related to public facilities, namely the right to accessibility to building, spatial and region and transportation. The conclusions presented in this article are, firstly, the right to accessibility is an integral part of the concept of human rights. Secondly, the right to accessibility to public facilities for persons with disabilities is accommodated in several laws and regulations in Indonesia.